Evaluation of different seed dormancy breaking methods including enzymatic assays for germination improvement in oil palm (Elaeis guineensis Jacq.) - Ghazali, Mohd Norsazwan; Sinniah, Uma Rani; Namasivayam, Parameswari (Malaysian Palm Oil Board, 2025)
The oil palm (Elaeis guineensis) is propagated by seeds for establishment in nurseries and commercial plantations. The seed is naturally dormant; thus, heat treatment is commercially used to alleviate this problem. This study evaluated eight seed dormancy breaking methods (operculum removal, 60 days storage, 60 days 40°C heat treatment, 120 days storage, 60 days storage + 40°C heat treatment, 180 days storage, 120 days storage + 40°C heat treatment and control) on seed germination, based on physical, morphological and physiological dormancy characteristics. Imbibition test indicated that less than 7% mass increment was recorded in all treatments. Germination of more than 82% was obtained for all heat-treated seeds with less than 13 days of mean germination time. The embryo was fully developed at 20 weeks after pollination, but applying heat treatment has accelerated its growth. The heat and storage treatments cause up to 36% reduction in peroxidase and 13% in catalase activities, with 9% (endosperm) and 26% (embryo) increment of α-amylase. It can be suggested that oil palm seeds exhibit a non-deep physiological dormancy, with heat treatment of 40°C as the most effective and practical dormancy-breaking method for commercial seed production.